(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2021)
In “Millions on the Move”, author Julia Tilton examines the impact climate change has on people. The paper, written for a first-year writing seminar in environmental science, focuses on rising sea levels and increasing temperatures in desert areas, exploring how these phenomena prompt the inhabitants of such regions to migrate. As research suggests, migration as a result of climate change will only increase in the coming decades if action is not taken to mitigate the consequences of a warming global climate. For additional context, listen to the author’s reflection on the piece below.